Using Democracy and Its Development - Wiratno (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to explore the implementation of democracy and its development. The term democracy, when viewed from an etymological point of view, comes from the words demos (people) and cratein (to rule). Thus, democracy means government by the people, which in its further development, as we saw in the Declaration of Independence, is